DESAIN MEDIA PEMBELAJARAN ICT BERBASIS PEDAGOGI HIJAU UNTUK MAHASISWA CALON GURU BIOLOGI FKIP UNIVERSITAS RIAU - Anisah Sayyidatina; Firdaus LN '; Darmadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Has conducted research for the development of media designInformation, Communication and Technology (ICT) -based Green Pedagogy for studentteachers of biology FKIP University of Riau. This study was conducted from January toJune 2015. This type of research is a kind of research development (Research andDevelopment), the procedural ADDIE development model. ADDIE developmentprocedures are implemented, namely Analysis, Design, Development and the trial waslimited. The results showed that the validation of ICT-based Learning Media PedagogyGreen to KD 1.1 to KD 1.4 total mean value validation is 3,29 (valid). For Web-basedvalidation Pedagogy Green to KD 1.1 to KD 1.4 total mean value validation is 3,24(valid). Based on the results of research conducted, it can be concluded that theLearning Media Green ICT-based pedagogy that has been developed as a supplementto the subject Environmental Education in Prodi. UR Biology category is valid and canbe implemented in the learning process.Key words: Design, Media learning ICT, Pedagogy Green